MB3W1 is an orthotopic xenograft model for anaplastic medulloblastoma displaying cancer stem cell- and Group 3-properties. Issue 1 (December 2016) - Dietl, Sebastian; Schwinn, Stefanie; Dietl, Susanne; Riedel, Simone; Deinlein, Frank; Rutkowski, Stefan; von Bueren, Andre; Krauss, Jürgen; Schweitzer, Tilmann; Vince, Giles; Picard, Daniel; Eyrich, Matthias; et al.
Abstract Background Medulloblastoma is the most common malignant brain tumor in children and can be divided in different molecular subgroups. Patients whose tumor is classified as a Group 3 tumor have a dismal prognosis. However only very few tumor models are available for this subgroup. Methods We established a robust orthotopic xenograft model with a cell line derived from the malignant pleural effusions of a child suffering from a Group 3 medulloblastoma. Results Besides classical characteristics of this tumor subgroup, the cells display cancer stem cell characteristics including neurosphere formation, multilineage differentiation, CD133/CD15 expression, high ALDH-activity and high tumorigenicity in immunocompromised mice with xenografts exactly recapitulating the original tumor architecture. Conclusions This model using unmanipulated, human medulloblastoma cells will enable translational research, specifically focused on Group 3 medulloblastoma.